2014
DOI: 10.1155/2014/865780
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Standard Protocols for Endodontic Treatment in North of KSA

Abstract: The objective of this study was to collect information regarding methods, materials, and attitudes employed during the endodontic treatment by dentists in north of Saudi Arabia. A questionnaire was designed and distributed among 300 dentists in north of Saudi Arabia to collect the data about the standard protocols of endodontic treatment. The collected data was analyzed by using the SPSS 10 computer software. Out of a total of 300 surveyed dentists, the 66% response rate showed that this study was true represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
4
27
0
2
Order By: Relevance
“…Endodontists with 16-20 years of activity were those who used magnification most frequently (65.2%). The findings also show that the adoption of new technologies by the professionals requires a certain time of activity, continuing education and training, with a long learning curve 10,12 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Endodontists with 16-20 years of activity were those who used magnification most frequently (65.2%). The findings also show that the adoption of new technologies by the professionals requires a certain time of activity, continuing education and training, with a long learning curve 10,12 .…”
Section: Discussionmentioning
confidence: 83%
“…Preference is related to the shorter length of treatment after the advent of nickel titanium files. However, other authors 7,12,18,22 found that most of the surveyed dentists preferred multiple endodontic treatment sessions. Whitten et al 23 argue that specialists opted for a single session while general practitioners preferred multiple sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies report a success rate of endodontic therapy ranging from 87.4% to 94.5% (19,20). Single-visit RCT has been recommended for use in cases with pulpal inflammation, traumatic pulpal exposure, and necrotic pulp with a sinus tract (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…Kök kanal tedavisinin başarısı; yeterli biyomekanik preperasyona ve mikroorganizmalar ile doku sıvılarının geçişini engelleyecek bir tıkaçlamaya bağlıdır (4). Bu amaca hizmet etmek maksadıyla, modern endodontide birçok yeni alet, materyal ve teknikler kullanıma girmektedir (5). Bu teknik ve ekipmanların doğru kullanılarak, tedavinin her aşamasının bilimsel çalışmalarla oluşmuş standartlara uygun yapılması, sonuçlar açısından büyük önem taşımaktadır.…”
Section: Introductionunclassified